KOMUNIKASI TANDA BADGE (EMBLEM) ANTARA KONSUMEN DAN PEMILIK TOKO ONLINE PADA MARKETPLACE - ADHI DHARMA SURIYANTO (Universitas Bina Sarana Informatika, 2017)
A very tough online business competition requires an appropriate way to win the competition to stay afloat by seizing the widest consumer market. Consumers should be able to determine the choice of where their money will be spent when they will transact online. One of the ways used by online store owners to communicate with consumers that aims to let consumers spend their money in their online store is the use of badge marks (emblems). A system created by bukalapak.com to improve the quality of lapak owners who open online stores in the marketplace.keywords: communication, badge marks (emblems), online store, marketplace